2013
DOI: 10.1021/om301246z
|View full text |Cite
|
Sign up to set email alerts
|

Borane-Catalyzed Si–H Activation Routes to Polysilanes Containing Thiolato Side Chains

Abstract: Dehydrocoupling and hydrosilation reactions of the Si−H bonds in poly(phenylsilane) catalyzed by B(C 6 F 5 ) 3 allow the preparation of new polymers containing both Si−H and Si−SR side chains. This postpolymerization modification takes place without any observable competing Si−Si bond cleavage, unlike other Lewis acid, transition-metal, or radical mediated routes. The −SR-functionalized polymers have been characterized by GPC, IR, UV−vis, elemental analysis, and 1 H, 13 C, and 29 Si NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…[8][9][10][11][12][13] Since then, others have developed applications in hydrostannylation, [14,15] silane dehydrocoupling, and silicone production and derivatization. [16][17][18][19][20][21][22][23][24][25] More recently, this electrophile has been exploited in "frustrated Lewis pair" (FLP) chemistry, acting as the Lewis acid partner in conjunction with bases to activate a wide variety of small molecules, including H 2 , CO 2 , olefins, [26] alkynes, [27] N 2 O, [28,29] and NO, [30] among others. [31] The application of this borane in FLP or "metalfree" hydrogenation catalysis [32] has drawn much attention.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] Since then, others have developed applications in hydrostannylation, [14,15] silane dehydrocoupling, and silicone production and derivatization. [16][17][18][19][20][21][22][23][24][25] More recently, this electrophile has been exploited in "frustrated Lewis pair" (FLP) chemistry, acting as the Lewis acid partner in conjunction with bases to activate a wide variety of small molecules, including H 2 , CO 2 , olefins, [26] alkynes, [27] N 2 O, [28,29] and NO, [30] among others. [31] The application of this borane in FLP or "metalfree" hydrogenation catalysis [32] has drawn much attention.…”
mentioning
confidence: 99%
“…Gevorgyan and co‐workers showed that 1 can also catalyze the hydrosilylation of polar C=C double bonds through the same Si−H bond activation process . This activation was also successfully applied in catalytic dehydrocoupling reactions between silanes and alcohols, thiols, and amines . We decided to use this activation in the chlorination of hydrosilanes through a dehydrocoupling reaction with HCl.…”
Section: Methodsmentioning
confidence: 98%
“…During their investigation of B(C 6 F 5 ) 3catalysed chemoselective postpolymerisation modication of poly(phenylsilane), Rosenberg and co-workers observed the formation of diphenylmethane as a result of overreduction of thiobenzophenone (31a). 57 The authors demonstrated that the desulfurisation of 31a with PhSiH 3 or Ph 2 SiH 2 as reductants occurred rapidly to furnish diphenylmethane (2c) in quantitative yield (Scheme 28).…”
Section: Boron Lewis Acids-catalysed Desulfurisationmentioning
confidence: 99%